2020 42nd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2020
DOI: 10.1109/embc44109.2020.9176229
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Quantification of White Matter Disconnection in the Human Brain

Abstract: With an estimated five million new stroke survivors every year and a rapidly aging population suffering from hyperintensities and diseases of presumed vascular origin that affect white matter and contribute to cognitive decline, it is critical that we understand the impact of white matter damage on brain structure and behavior. Current techniques for assessing the impact of lesions consider only location, type, and extent, while ignoring how the affected region was connected to the rest of the brain. Regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…For each significant LV, we chose a maximum of 3 regions of spatially connected voxels with large weights in order to individually identify the set of streamlines passing through them. This approach is identical to that used in identifying the network effects of brain lesions (Karnath et al, 2018; Talozzi et al, 2023; Thiebaut de Schotten et al, 2020; Zayed et al, 2020). Here, we used a previously constructed streamline connectivity model that consisted of 10 million representative streamlines between all GM regions in our template space.…”
Section: Methodsmentioning
confidence: 99%
“…For each significant LV, we chose a maximum of 3 regions of spatially connected voxels with large weights in order to individually identify the set of streamlines passing through them. This approach is identical to that used in identifying the network effects of brain lesions (Karnath et al, 2018; Talozzi et al, 2023; Thiebaut de Schotten et al, 2020; Zayed et al, 2020). Here, we used a previously constructed streamline connectivity model that consisted of 10 million representative streamlines between all GM regions in our template space.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, structural disconnectome has been proposed to characterize the disruptions caused by local lesions on connectivity by spatially mapping white matter fiber tracts with regional brain lesions (Carolyn D. Langen et al, 2017 ; Zayed et al, 2020 ). Studies using 3714 participants from Rotterdam Study found that WMH‐related disconnectome was especially related to worse executive functioning and concluded that WMH‐related disconnectome explains more variation in cognitive function than regional lesion volumes (C. D. Langen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%